The Trade-Offs of The Deagrarianisation Processes in a Conservation Area: A Case Study of The Nida Landscape Park, Poland - Kamila MUSIAL (Communications of International Proceedings, 2022)
In the area of the Nida Landscape Park there are 10 different rural and municipal communes. The research was carried out in 2020, in all that communes, where agricultural activities still are or traditionally were present. The study was conducted in the form of a surveys, in order to assess the agricultural aspects of such areas. Results show that in fact the large share of conservation areas in a given commune located in the Nida Landscape Park favor the deagrarianisation processes. It is so, because in fact also different protected areas are within the boundaries of that landscape park, or just in the immediate vicinity. It was true for the Busko Zdrój, with 13 conservation areas, where a share of the abandoned agricultural land was high (over 50%), and the share of farms without livestock was about 60%. A similar phenomenon was observed in the Pińczów commune, with the total number of 25 conservation areas, where farms without livestock made up 50% of the total number of farms, and 30% of the agricultural land was extensified. In order to achieve certain compromises between farmers engaged in agricultural production in protected areas, and existing requirements for such activity, certain conditions should be met, like moderation and less radicalisation of the laws concerning the conservation areas.
Keywords: protected areas; abandonment of agricultural land; Świętokrzyskie Region